Extramedullary hematopoiesis and paraplegia in a patient with hemoglobin e-Beta thalassemia - Alam, MR; Habib, MS; Dhakal, GP; Khan, MR; Rahim, MA; Chowdhury, AJ; Mahmud, TK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):452-7 The abstract of this article is available on the PubMed website